2022
DOI: 10.1109/jtehm.2022.3144037
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Seizure Prediction in Scalp EEG Using a Multi-Scale Neural Network With Dilated Convolutions

Abstract: Objective: Epileptic seizure prediction based on scalp electroencephalogram (EEG) is of great significance for improving the quality of life of patients with epilepsy. In recent years, a number of studies based on deep learning methods have been proposed to address this issue and achieve excellent performance. However, most studies on epileptic seizure prediction by EEG fail to take full advantage of temporal-spatial multi-scale features of EEG signals, while EEG signals carry information in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…We also compare our MViT approach with other concurrent and recently-developed deep learning methods that either use CNN [ 23 , 24 , 43 , 47 , 49 , 54 ] or long short-term memory (LSTM) [ 42 , 44 ] for epileptic seizure prediction. In [ 23 ], the raw EEG signals were converted to 3D wavelet tensors (time × scales × channels) and fed into a CNN model, which achieved a prediction sensitivity of 86.6% and a FPR of 0.147/h.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also compare our MViT approach with other concurrent and recently-developed deep learning methods that either use CNN [ 23 , 24 , 43 , 47 , 49 , 54 ] or long short-term memory (LSTM) [ 42 , 44 ] for epileptic seizure prediction. In [ 23 ], the raw EEG signals were converted to 3D wavelet tensors (time × scales × channels) and fed into a CNN model, which achieved a prediction sensitivity of 86.6% and a FPR of 0.147/h.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that both seizure-prediction sensitivity and FPR were considerably improved to 92.0% and 0.12, respectively. More recently, several studies have demonstrated that CNN-based models can be also effectively applied to raw EEG signals and achieve comparable prediction performance with a sensitivity of 92.0–98.8% [ 47 , 49 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this assessment, all out 5000 unique sections were separated from this dataset, and were partitioned into 60:40 proportion for preparing and testing individually. Results were assessed regarding exactness, accuracy, review and deferral, and were contrasted and TTFC [4], NNM [5], and LBP TH [9] for approval purposes. The outcomes for exactness can be seen from table 1 as follows,…”
Section: Results Analysis and Comparisonmentioning
confidence: 99%
“…A wide collection of EEG portrayal models is proposed by researchers all through the long haul, and all of them vary similar to congruity, exactness, survey, accuracy and concede execution. For instance, work in [2,3,4] analyzes plan of reduced direction set (RISC)-V convolutional Neural Network (CNN) Coprocessor, blend of direct discriminant examination (LDA), k Nearest Neighbor (KNN), support vector machine (SVM), and counterfeit brain organization (ANN) with ordinary spatial model (CSP), and Transfer TSK Fuzzy Classifier (TTFC) for achieving better portrayal results. These models have incredible precision, yet need terms of exactness execution due to their application-unequivocal portrayal characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%